Kidding ourselves : the hidden power of self-deception - Hallinan, Joseph T. (New York : Crown Publishers, 2014)
To one degree or another, we all misjudge reality. Our perception--of ourselves and the world around us--is much more malleable than we realize. This self-deception influences every major aspect of our personal and social life, including relationships, sex, politics, careers, and health.
The Pulitzer Prize-winning author of Why We Make Mistakes presents an analysis of the human inclination toward self-deception that explains how selective misperception influences every major aspect of life, has powerful placebo effects and does not always have negative consequences.
Pt.I The power of nothing: placebos, mass hysteria, and fatal delusions -- Pt.II The eye of the beholder: perception, expectation, and the lure of superstition -- Pt.III Delusions of success: power, money, and risk.
Includes bibliographical references (pages 213-253) and index.
Keywords: Self-deception.